Analisis Semiotika Michael Riffaterre pada Puisi Īkbarī ‘Īsyrīna ‘Ᾱman Karya Nizar Qabbani / Michael Riffaterre’s Semiotic Analysis on the Poetry Ikbarī ’Īsyrīna ’Ᾱman by Nizar Qabbani - Haikal, Yusuf (Diwan: Jurnal Bahasa dan Sastra Arab, 2021)
الهدف من هذا البحث هو تقديم لمحة عامة عن تطبيق التحليل السيميائي لمايكل ريفاتير على قصيدة "إكبري عشرين عاما" لنزار قباني. المنهج المستخدم هو المنهج الوصفي النوعي. ومن خلال هذا المنهج، يتم أخذ البيانات والدراسات من مصادر مختلفة ويتم تحليلها بعد ذلك باستخدام السيميائية لريفاتير، أي من خلال النظر في عدم مباشرة التعبير وتحديد النموذج(model) والنوع(variant) والمصفوفة(matrix) ، بعد قراءة الإستكشافية والتأويلية سابقًا. وتم وصف نتائج التحليل وتقديمها في شكل كلمات. أما الموضوع من هذا البحث يشمل النص من قصيدة "اكبري عشرين عاما"، وكذا المعنى والمصفوفة من هذه القصيدة. استنادًا إلى تحليل ريفاتير السيميائية، يمكن الكشف عن أن المعنى الشامل لهذه القصيدة يتعلق برجل يحب فتاة صغيرة عمرها أقل منه بكثير، وهذا يظهر إحساسًا قويًا بالحب في نزار بحيث يمكنه تأليف قصائد جميلة جدًا بسبب ذلك. وتم الحصول على المعنى بناءً على القراءة التأويلية التي يعززها نموذج "عشقا" الذي يحتوي على ثلاثة أنواع، وهي الانتظار، والوقت والعمر، والاجتماع. مصفوفة هذه القصيدة هي "أمل الرجل واعتقاده بأنه بعد عشرين عامًا من الآن سيكون قادرًا على أن يحب الفتاة الصغيرة التي كان يحبها منذ هذا الوقت". تحتوي هذه القصيدة على هيفوغرام مع قصيدة نزار أخرى، يعني "أحبك". الكلمات المفتاحية: السيميائي؛ ريفاتير؛ نزار قباني؛ اكبري عشرين عاما. Abstract: This research aims to describe the overview of Michael Riffaterre’s semiotic analysis to the poem Ikbarῑ ’Ῑsyrῑna ’Ᾱman by Nizar Qabbani. The research method is descriptive qualitative which the data and studies are based on various sources, which are then analyzed using a semiotic approach and Riffaterre’s theory by looking at the indirectness of expressions, models, variants, matrices, and hypograms based on the previous reading heuristically and hermeneutically. The results analysis is described and presented in the words form. The subject of the research is the poem Īkbarῑ Īsyrῑna ’Āman, while the object of research is the meaning or matrix in the poem Īkbarῑ Īsyrῑna ’Āman. This researcher based the analysis on Riffaterre’s semiotic reading, which revealed that the holistic meaning of this poem is about a man who loves a girl who is still young and has different age from him. This research shows a strong sense of love in Nizar so that he can compose poetry in a very beautiful way. The meaning is obtained based on hermeneutic reading, which is strengthened by the "falling in love" model, which has 3 variants, namely: waiting, time and age, and meeting. The matrix of this poem is "the expectation and belief of a man that he can gain his love with the young girl in the twenty years later". This poem consisted of hypogram text that related to another Nizar’s poem, Uchibbuka.